An Exploratory Study on Chinese Females' Social Media Self-Presentation: A Case Study of WeChat - Ting Yang; Sangho Seo (Asian Journal for Public Opinion Research)
Based on Goffman's dramaturgical theory and self-objectification framework, this study examined: 1) Chinese female's WeChat self-presentation, 2) the impact of WeChat usage on female self-objectification, and 3) the impact of self-objectification on WeChat self-presentation tactics. An online survey was conducted. The main findings include: 1) most of the participants chose to beautify their pictures and videos before they posted them, 2) the respondents attached higher importance to appearance-based body attributes than competence-based ones, 3) the most frequently applied self-presentation tactic was ingratiation, 4) WeChat usage was not a predictor of Chinese women's self-objectification, and, 5) along with extroversion, self-objectification had an impact on ingratiation, supplication, self-promotion, and exemplification. Meanwhile, use of the electronic curtain and audience sifting to control who can see a post and for how long demonstrated the empowerment of the users when they conduct self-presentation.